Genetic Diversity of Histoplasma capsulatum Strains Isolated from Soil, Animals, and Clinical Specimens in Rio de Janeiro State, Brazil, by a PCR-Based Random Amplified Polymorphic DNA Assay - Muniz, Mauro de Medeiros (American Society for Microbiology, 2001)
Little is known about the genetic strain diversity and geographical range of Histoplasma capsulatum isolated in Rio de Janeiro State, Brazil. We characterized 13 environmental, 7 animal, and 28 clinical H. capsulatum isolates by using a PCR-based random amplified polymorphic DNA (RAPD) assay. DNA fingerprinting of these soil, animal, and clinical specimens was performed with four primers (1253, 1281, D-9355, and D-10513) and generated amplicons with considerable polymorphism. Although all of the isolates exhibited more than 80% genetic relatedness, they could be clustered into four to six genotypes for each primer. The RAPD profiles of H. capsulatum isolated from Rio de Janeiro State could be distinguished from those of the U.S. strains included in this study (Downs, G222B, G-186B, and FLS1) by showing less than 70% similarity to each primer. The genetic polymorphisms between H. capsulatum strains isolated from animals and soil obtained in the same geographic areas were 100% similar, suggesting that an environmental microniche could be acting as a source of infection for animals and the local human population.